Seni Prasi Dalam Kajian Antopologi Dan Sosiologi - I Nyoman Lodra (Jurnal Budaya Nusantara, 2017)
Pracy Art is a kind of painting using leaf lontar media which is painted with the sharp iron, the formercharcoal mixed with coconut oil slightlyy on its surface. Themes are revealed; Mahabrata, Ramayana, Sotasoma,Tantri, and other folklore. The existence of the palm leaf is important in the life of the people of Geriya, Talibeng,Sidemen, Karangasem. Because the art is part of the civilization of Ancient Bali. To understand more deeply aboutthis art of pracy it is necessary to approach with anthropology and Sociology. Both fields of science are related to humanlife in the activity of art. This Study the focuses on the discussion in "literature", collectors, and community observers ofpracy art. The purpose of the research is to know the existence of art pracy in the life of Geriya, Taliban, Karangasemsociety. The benefit of research is to know existence of pracy art at Bali ancient, and in global era. The research methoduses qualitative discriminative, ethnographic approach, data retrieval with observation, interview, and documentation.To solve the problem in the art of pracy use some big theories; ethnographic theory, social exchange, diffusion theory andother small theories. The Findings show that Pracy Art in the life of Geriya Taliban, Karangasem is as arepresentation of beliefs, beliefs and teachings of Hinduism.